Analisis Faktor dalam Pengambilan Keputusan Nasabah Memilih Produk Pembiayaan Perbankan Syariah (Studi Kasus pada PT Bank Syariah Mandiri Cabang Ciputat) - Zulkifli Zainuddin; Yahya Hamja; Siti Hamidah Rustiana (Jurnal Keuangan dan Perbankan, 2016)
The purpose of this study are to determine (a) the factors that influence  client's decision while choosing the financial products and (b) factors which have dominant influence to client's decision on financing in PT Bank Syariah Mandiri, Ciputat. The population in this study are all people who doing business in Ciputat and customers who need finance from Bank Syariah Mandiri,  Branch of Ciputat. By using convenience sampling methods, this research has been generated 100 respondents. This research used factor analysis to analyze the datas. The results indicate that the marketing mix variable has the highest value of loading factor in the decision making process.